Efficacy and safety of risankizumab in moderate-to-severe plaque psoriasis (UltIMMa-1 and UltIMMa-2): results from two double-blind, randomised, placebo-controlled and ustekinumab-controlled phase 3 trials. Issue 10148 (25th August 2018) - Gordon, Kenneth B; Strober, Bruce; Lebwohl, Mark; Augustin, Matthias; Blauvelt, Andrew; Poulin, Yves; Papp, Kim A; Sofen, Howard; Puig, Lluís; Foley, Peter; Ohtsuki, Mamitaro; Flack, Mary; et al.
Summary: Background: Risankizumab is a humanised IgG1 monoclonal antibody that binds to the p19 subunit of interleukin-23, inhibiting this key cytokine and its role in psoriatic inflammation. We aimed to assess the efficacy and safety of risankizumab compared with placebo or ustekinumab in patients with moderate-to-severe chronic plaque psoriasis. Methods: UltIMMa-1 and UltIMMa-2 were replicate phase 3, randomised, double-blind, placebo-controlled and active comparator-controlled trials done at 139 sites in Australia, Austria, Belgium, Canada, Czech Republic, France, Germany, Japan, Mexico, Poland, Portugal, South Korea, Spain, and the USA. Eligible patients were 18 years or older, with moderate-to-severe chronic plaque psoriasis. In each study, patients were stratified by weight and previous exposure to tumour necrosis factor inhibitor and randomly assigned (3:1:1) by use of interactive response technology to receive 150 mg risankizumab, 45 mg or 90 mg ustekinumab (weight-based per label), or placebo. Following the 16-week double-blind treatment period (part A), patients initially assigned to placebo switched to 150 mg risankizumab at week 16; other patients continued their originally randomised treatment (part B, double-blind, weeks 16–52). Study drug was administered subcutaneously at weeks 0 and 4 during part A and at weeks 16, 28, and 40 during part B. Co-primary endpoints were proportions of patients achieving a 90% improvement in the Psoriasis Area Severity Index (PASI 90) and a static Physician's Global Assessment (sPGA) score of 0 or 1 at week 16 (non-responder imputation). All efficacy analyses were done in the intention-to-treat population. These trials are registered with ClinicalTrials.gov, numbers NCT02684370 (UltIMMa-1) and NCT02684357 (UltIMMa-2), and have been completed. Findings: Between Feb 24, 2016, and Aug 31, 2016, 506 patients in UltIMMa-1 were randomly assigned to receive 150 mg risankizumab (n=304), 45 mg or 90 mg ustekinumab (n=100), or placebo (n=102). Between March 1, 2016, and Aug 30, 2016, 491 patients in UltIMMa-2 were randomly assigned to receive 150 mg risankizumab (n=294), 45 mg or 90 mg ustekinumab (n=99), or placebo (n=98). Co-primary endpoints were met for both studies. At week 16 of UltIMMa-1, PASI 90 was achieved by 229 (75·3%) patients receiving risankizumab versus five (4·9%) receiving placebo (placebo-adjusted difference 70·3% [95% CI 64·0–76·7]) and 42 (42·0%) receiving ustekinumab (ustekinumab-adjusted difference 33·5% [22·7–44·3]; p<0·0001 vs placebo and ustekinumab). At week 16 of UltIMMa-2, PASI 90 was achieved by 220 (74·8%) patients receiving risankizumab versus two (2·0%) receiving placebo (placebo-adjusted difference 72·5% [95% CI 66·8–78·2]) and 47 (47·5%) receiving ustekinumab (ustekinumab-adjusted difference 27·6% [16·7–38·5]; p<0·0001 vs placebo and ustekinumab). In UltIMMa-1, sPGA 0 or 1 at week 16 was achieved by 267 (87·8%) patients receiving risankizumab versus eight (7·8%) receiving placebo (placebo-adjusted difference 79·9% [95% CI 73·5–86·3]) and 63 (63·0%) receiving ustekinumab (ustekinumab-adjusted difference 25·1% [15·2–35·0]; p<0·0001 vs placebo and ustekinumab). In UltIMMa-2, 246 (83·7%) patients receiving risankizumab versus five (5·1%) receiving placebo (placebo-adjusted difference 78·5% [95% CI 72·4–84·5]) and 61 (61·6%) receiving ustekinumab achieved sPGA 0 or 1 at week 16 (ustekinumab-adjusted difference 22·3% [12·0–32·5]; p<0·0001 vs placebo and ustekinumab). The frequency of treatment-emergent adverse events in UltIMMa-1 and UltIMMa-2 was similar across risankizumab (part A: 151 [49·7%] of 304 and 134 [45·6%] of 294; part B: 182 [61·3%] of 297 and 162 [55·7%] of 291), placebo (part A: 52 [51·0%] of 102 and 45 [45·9%] of 98), ustekinumab (part A: 50 [50·0%] of 100 and 53 [53·5%] of 99; part B: 66 [66·7%] of 99 and 70 [74·5%] of 94), and placebo to risankizumab (part B: 65 [67·0%] of 97 and 61 [64·9%] of 94) treatment groups throughout the study duration. Interpretation: Risankizumab showed superior efficacy to both placebo and ustekinumab in the treatment of moderate-to-severe plaque psoriasis. Treatment-emergent adverse event profiles were similar across treatment groups and there were no unexpected safety findings. Funding: AbbVie and Boehringer Ingelheim.